QUALITY TRANSFORMATION STRATEGY THROUGH THE INTEGRATION OF LEARNER VISION AND INSTRUCTIONAL LEADERSHIP IN ELEMENTARY SCHOOLS - Zumrotun Zumrotun; Ngurah Ayu Nyoman Murniati; Supandi (SOSIOEDUKASI, 2026)
The shift in the global education paradigm demands holistic learning quality beyond quantitative achievement. Despite having ICT-literate educators, SD Negeri 1 Godong faces the challenge of numeracy stagnation (70.83%) and character fluctuations. This research is a qualitative case study aimed at analyzing the development of vision, culture, and learning leadership in improving educational quality. Data were collected through interviews, observations, and Education Report Card documents, then analyzed using the interactive model of Miles et al. The results show that the vision of the "Center for Literacy and Technology" has been institutionalized, but teachers' use of ICT is still visual-passive and therefore has not optimally boosted numeracy. The principal's leadership has been proven to be supportive of teacher self-efficacy, but requires strengthening of cognitive activation-based clinical supervision. It is concluded that sustainable quality requires the synergy of digital innovation, character strengthening, and logical reasoning simultaneously by instructional leadership.